Metabolic syndrome and increased susceptibility to renal cell carcinoma – a meta-analysis - Yanyu Zhou; Yujun Chen; Heng Yang; Zhiqi Xu; Jinbiao Zhuang; Qitao Bian; Gongxian Wang (BMC Nephrology)
Abstract Background Metabolic syndrome (MetS) has been demonstrated to be associated with various types of cancer, but its specific relationship with kidney cancer remains inconclusive. Therefore, this study conducts a Meta-analysis to systematically evaluate the potential link between metabolic syndrome and the risk of kidney cancer development. Methods Observational studies were retrieved from PubMed, Embase, Cochrane Library, and Web of Science. Two independent reviewers extracted study characteristics and assessed the quality of the studies. A random-effects model was employed to account for heterogeneity, and subgroup analyses were conducted to explore the impact of study characteristics on the results. Publication bias was evaluated using funnel plot symmetry and Egger’s regression test. Results Six studies were included, with 10 results extracted for the Meta-analysis. The findings indicated that MetS is an independent risk factor for kidney cancer (HR: 1.44, 95% CI: 1.31–1.59, P < 0.001). Heterogeneity between studies was significant (Cochran’s Q test, P < 0.001; I2 = 83.7%), indicating substantial variability. Subgroup analyses revealed consistent associations across gender, follow-up duration, and MetS diagnostic criteria (P > 0.05), but significant variations by race and study design (P < 0.05). The funnel plot appeared symmetrical, and Egger’s regression test (P = 0.425) confirmed a low risk of publication bias. Conclusion MetS is independently associated with an increased susceptibility to RCC in the adult population, although the strength of this association varies across different study designs and regions due to the observed heterogeneity.